Resurfaced versus Non-Resurfaced Patella in Total Knee Arthroplasty - Allen, William; Eichinger, Josef; Friedman, Richard (The Journal of Knee Surgery, 2019)
The prevalence of knee osteoarthritis is increasing, as is the projected use of total knee arthroplasty (TKA) to treat severe cases that fail to respond to conservative measures. Implant designs are either cruciate retaining or posterior stabilized, and while both have high success rates, management of the patella still remains a controversial topic. Although studies indicate that resurfacing the patella provides no significant clinical differences compared with non-resurfacing techniques, surgeons continue to resurface the patella during TKA. Rates of patella resurfacing continue to be as high as 90% in the United States, while European countries tend to favor non-resurfacing techniques. The purpose of this article is to discuss relevant research on patella resurfacing during TKA, to compare the results, and give evidence-based recommendations on how it should be approached going forward.
Keywords: patella; total knee arthroplasty; patella resurfacing; resurfaced patella; non-resurfaced patella